1980
DOI: 10.1002/bjs.1800670416
|View full text |Cite
|
Sign up to set email alerts
|

The use of Silastic foam dressing in the treatment of advanced hidradenitis suppurativa

Abstract: We describe our experience in the use of a Silastic foam dressing in I7 patients undergoing radical excision of hidradenitis suppurativa whose wounds were allowed to heal by granulation. Axillary excisions were carried out in 9 patients and perineal excisions in 8 patients. The technique permits adequate excision of the disease and results in a cosmetically acceptable scar, superior to that obtained by skin grafting and with little limitation of movement. It avoids the pain of conventionalmanagement of granula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This means that in those patients for whom primary skin closure is chosen there must be a certain degree of compromise in the extent of the excision margin, which increases the risk of recurrence. Of course, a rather more extensive defect can heal by secondary intention, and indeed Morgan et al reported favourable results in 10 patients with axillary disease (19,20). The drawback to healing by secondary intention is, however, a long period of healing taking maybe several weeks or more (9).…”
Section: Discussionmentioning
confidence: 99%
“…This means that in those patients for whom primary skin closure is chosen there must be a certain degree of compromise in the extent of the excision margin, which increases the risk of recurrence. Of course, a rather more extensive defect can heal by secondary intention, and indeed Morgan et al reported favourable results in 10 patients with axillary disease (19,20). The drawback to healing by secondary intention is, however, a long period of healing taking maybe several weeks or more (9).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of secondary healing, scarring has not been reported. [146][147][148] For large lesions this method is slow, and, even though modern bandaging provides good clinical results and improved ease of management, morbidity can still be considerable for a protracted period. Healing periods of several months can be expected following large excisions.…”
Section: The Methods Of Closurementioning
confidence: 99%
“…Many surgeons prefer this method . Some authors have also advocated the use of Silastic foam elastomer dressing in the postoperative management of these patients . Morgan compared skin healing by grafting with secondary‐intention healing with Silastic foam dressing and found that secondary‐intention healing led to good cosmetic results and low recurrence rates and avoided the need for immobilization and a painful donor site; most patients in this series preferred Silastic foam dressing over skin grafting .…”
Section: Surgical Managementmentioning
confidence: 94%